From contact to connection: a comprehensive examination of affective touch in educational settings - El Hakim, Sonia; Farsani, Danyal (Frontiers in Psychology, 2024)
We often talk about the way we talk, and we frequently try to see the way we see, but for some reasons we have rarely touched on the way we touch (Morris, personal Communication 2016). The communication we transmit with touch is perceived to be one of the most powerful means of establishing human relationships. In particular, tactile communication with parents, caregivers and teachers is particularly important for infants and students (Johansson et al., 2021; Keränen & Uitto, 2023), as it helps make stronger relationships between educators or teachers and schoolers and also between students (Vincent et al., 2023). Research has demonstrated the numerous benefits that an affective touch has on students, physically, socially and cognitively, or as Manning (2007) has observed, touch touches deeper that just one´s skin and it is a recipe for creating meaningful relations. However, in the educational context, touch is perceived to be a complex phenomenon full of tension and emotion. For years, a dilemma has arisen in educational institutions in some countries, whether teachers can touch students or not? Despite the benefits that affective touch brings to students, cases of sexual abuse and inappropriate behavior at school have alerted the education system, to such an extent that many teachers worldwide consider what is and is not appropriate when communicating affectively with their students through touch (Johansson et al., 2021; Owen and Gillentine, 2011). In this perspective article, by drawing on previous literature reviews, we shall highlight the benefits that affective touch has on learners.